Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Communication behavior of the snow leopard (Panthera uncia): understanding marking-behavior patterns to optimize camera-trapping studies - Miha Krofel; Teresa Oliveira; Francesco Rovero; Claudio Groff; Claudio Augugliaro; Valentina Oberosler; Maximilian L. Allen (Behavioral Ecology and Sociobiology, 2025)
Many carnivores rely on marking behavior for intraspecific communication with potential mates and competitors, using scent and visual markings to advertise their use of a territory and allow potential mates to assess their quality. However, obtaining data on communication behaviors of rare and elusive animals can be challenging. To better understand marking behavior of snow leopard ( Panthera uncia ), we combined camera-trapping, snow-tracking and transect counts of scrapes in the Altai Mountains, Mongolia, and measured frequencies of communication behaviors in both space and time. Next, we explored if this information could be used to improve the efficiency of snow leopard population monitoring through camera-trapping. Using the combination of all three methods, we detected seven communication behaviors. Most visits at marking sites began with sniffing (recorded at 56.4% visits) before progressing to other behaviors. Urine spraying (17.7% of visits) and scraping (16.8%) were exhibited at significantly more visits than other communication behaviors (flehmen, head/body rubbing, fecal deposition, claw marking). According to the snow-tracking data conducted in optimal habitats, scraping was the most frequent marking behavior with 12.8 scrapes/km, followed by urine marking with 10.5 marks/km. Along 32 transects, we recorded a mean of 8.0 cumulative scrapes/km, with highest marking rates recorded in gorges, which we recommend as prime habitats for deploying camera-traps. Finally, our results suggest that the number of scrapes observed at potential camera-trapping sites represents a good predictor of snow leopard visitation rate. Therefore, this parameter can be used when choosing camera-trapping locations to increase the efficiency of monitoring programs.

Human Footprint and Forest Disturbance Reduce Space Use of Brown Bears ( Ursus arctos ) Across Europe - Anne G. Hertel; Aida Parres; Shane C. Frank; Julien Renaud; Nuria Selva; Andreas Zedrosser; Niko Balkenhol; Luigi Maiorano; Ancuta Fedorca; Trishna Dutta; Neda Bogdanović; Natalia Bragalanti; et al. (Global Change Biology, 2025)
Three‐quarters of the planet's land surface has been altered by humans, with consequences for animal ecology, movements and related ecosystem functioning. Species often occupy wide geographical ranges with contrasting human disturbance and environmental conditions, yet, limited data availability across species' ranges has constrained our understanding of how human pressure and resource availability jointly shape intraspecific variation of animal space use. Leveraging a unique dataset of 758 annual GPS movement trajectories from 375 brown bears ( Ursus arctos ) across the species' range in Europe, we investigated the effects of human pressure (i.e., human footprint index), resource availability and predictability, forest cover and disturbance, and area‐based conservation measures on brown bear space use. We quantified space use at different spatiotemporal scales during the growing season (May–September): home range size; representing general space requirements, 10‐day long‐distance displacement distances, and routine 1‐day displacement distances. We found large intraspecific variation in brown bear space use across all scales, which was profoundly affected by human footprint index, vegetation productivity, and recent forest disturbances creating opportunity for resource pulses. Bears occupied smaller home ranges and moved less in more anthropized landscapes and in areas with higher resource availability and predictability. Forest disturbances reduced space use while contiguous forest cover promoted longer daily movements. The amount of strictly protected and roadless areas within bear home ranges was too small to affect space use. Anthropized landscapes may hinder the expansion of small and isolated populations, such as the Apennine and Pyrenean, and obstruct population connectivity, for example between the Dinaric Pindos population and the Alpine or Carpathian population. Our findings call for actions to maintain bear movements across landscapes with high human footprint, for example by maintaining forest integrity, to support viable bear populations and their ecosystem functions.

Isotopic signature in isolated south-western populations of European brown bear (Ursus arctos) - Ana García-Vázquez; Denise A. Crampton; Angela L. Lamb; George A. Wolff; Kostas Kiriakoulakis; Giulia Guidarelli; Anna Loy; Paolo Ciucci; Claudio Groff; Ana C. Pinto-Llona; Aurora Grandal-d’Anglade; Carlo Meloro (Mammal Research, 2023)
Stable isotope analysis of animal tissue samples is increasingly used to study the trophic ecology of target species. The isotopic signatures respond to the type of diet, but also to the environmental conditions of their habitat. In the case of omnivorous, seasonal or opportunistic feeding species, the interpretation of isotopic values is more complex, as it is largely determined by food selection, either due to individual choice or because of availability. We analysed C and N isotopes in brown bear ( Ursus arctos ) hair from four isolated populations of south-western Europe (Cantabrian, Pyrenees, Central Apennines and Alpine) accounting for the geographical and climatic differences among the four areas. We found inter-population differences in isotopic signatures that cannot be attributed to climatic differences alone, indicating that at least some bears from relatively higher altitude populations experiencing higher precipitation (Pyrenees) show a greater consumption of animal foods than those from lower altitudes (Cantabrian and Apennines). The quantification of isotopic niche space using Layman’s metrics identified significant similarities between the Cantabrian and Central Apennine samples that markedly differ from the Pyrenean and Alpine. Our study provides a baseline to allow further comparisons in isotopic niche spaces in a broad ranged omnivorous mammal, whose European distribution requires further conservation attention especially for southern isolated populations.

First spatially-explicit density estimate for a snow leopard population in the Altai Mountains - Valentina Oberosler; Simone Tenan; Claudio Groff; Miha Krofel; Claudio Augugliaro; Bayaraa Munkhtsog; Francesco Rovero (Biodiversity and Conservation, 2022)

Evaluating mortality rates with a novel integrated framework for nonmonogamous species - Simone Tenan; Aaron Iemma; Natalia Bragalanti; Paolo Pedrini; Marta De Barba; Ettore Randi; Claudio Groff; Meritxell Genovart (Conservation Biology, 2016)
The conservation of wildlife requires management based on quantitative evidence, and especially for large carnivores, unraveling cause‐specific mortalities and understanding their impact on population dynamics is crucial. Acquiring this knowledge is challenging because it is difficult to obtain robust long‐term data sets on endangered populations and, usually, data are collected through diverse sampling strategies. Integrated population models (IPMs) offer a way to integrate data generated through different processes. However, IPMs are female‐based models that cannot account for mate availability, and this feature limits their applicability to monogamous species only. We extended classical IPMs to a two‐sex framework that allows investigation of population dynamics and quantification of cause‐specific mortality rates in nonmonogamous species. We illustrated our approach by simultaneously modeling different types of data from a reintroduced, unhunted brown bear ( Ursus arctos ) population living in an area with a dense human population. In a population mainly driven by adult survival, we estimated that on average 11% of cubs and 61% of adults died from human‐related causes. Although the population is currently not at risk, adult survival and thus population dynamics are driven by anthropogenic mortality. Given the recent increase of human‐bear conflicts in the area, removal of individuals for management purposes and through poaching may increase, reversing the positive population growth rate. Our approach can be generalized to other species affected by cause‐specific mortality and will be useful to inform conservation decisions for other nonmonogamous species, such as most large carnivores, for which data are scarce and diverse and thus data integration is highly desirable.

Long-distance dispersal connects Dinaric-Balkan and Alpine grey wolf (Canis lupus) populations - Nina Ražen; Alessandro Brugnoli; Chiara Castagna; Claudio Groff; Petra Kaczensky; Franci Kljun; Felix Knauer; Ivan Kos; Miha Krofel; Roman Luštrik; Aleksandra Majić; Georg Rauer; et al. (European Journal of Wildlife Research, 2016)